Analisis Karya Arsitektur Kantor Pos Medan dan Pendekatan Kode Semiotika pada Bangunan - Majid, Irfan; Sagala, Peranita (Jurnal Teknik dan Teknologi Indonesia, 2026)
The Medan Post Office is a heritage building that remains in operation today. It was constructed under the Dutch East Indies government between 1909 and 1911, designed by Dutch architect Ir. Simon Snuyf, and once symbolized the economic advancement of colonial-era Medan. Standing in the Kesawan heritage district, the building reflects Functional Modern architecture, known locally as Geometric Art Deco, and is closely tied to the growth of the tobacco plantation trade and the colonial transportation infrastructure that supported it. This study aims to trace the history of the building, identify its architectural style and characteristics, and examine it through a semiotic-code approach, namely the study of signs bound to the social codes through which meaning is collectively understood. Primary data were obtained through field surveys of the building and interviews with its management and surrounding community, complemented by secondary data from journals, print media, and reputable online sources. Findings show that the building's hermeneutic, semantic, symbolic, proairetic, and cultural codes, together with its aesthetic qualities of unity, balance, proportion, and heroic scale, continue to define its identity as a colonial-era landmark, now adaptively reused as the creative hub Pos Bloc Medan.